Mechanical and performance properties of re-vulcanized blends of GTR/NR. Issue 2 (May 2023) - Zitzumbo, R; Becerra, María B; Padilla-Rizo, Beatriz; Estrada-Monje, Anayansi; Alonso-Romero, Sergio
The effect of natural rubber (NR) on the mechanical and performance properties of ground tire rubber (GTR) has been investigated. The mechanical properties of vulcanized GTR/NR blends were determined in a universal testing machine. It was found a decreasing in the mechanical properties of the GTR/NR blends as the number of re-vulcanization processes increases. This behavior was attributed to the decrease in the concentration on GTR in the vulcanized GTR/NR blend with respect to the next one, and to a structural net degradation into the re-vulcanized GTR/NR blend due to the reversion process (over vulcanization). In the loss modulus charts was observed that the peaks of the curves got smaller and wide as the re-vulcanization process increased, due to the mechanical loses and elastic gains of the GTR/NR re-vulcanized blends. On the other hand, in the performance results was found that the cut growth values of Flexion Ross were more affected by the thickness of the plaque of vulcanized rubber than for the number of re-vulcanization processes of the GTR/NR blend. In addition, as the re-vulcanization processes increased, the structural degradation of the tridimensional cross-linked net, increased as well, more severely from the fourth re-vulcanization process. It could be concluded that the GTR/NR blends with high GTR content, could be used in the sole shoe fabrication, taking care that the thickness is ≤ 4.5 mm, and that the GTR/NR blends have not been subjected to more than two re-vulcanization processes.